PELAKSANAAN PEMBUATAN KTP ELEKTRONIK (E-KTP) KEPADA MAYARAKAT DITINJAU DARI PERATURAN PRESIDEN RI NOMOR 67 TAHUN 2011 DI KECAMATAN LONG BAGUN KABUPATEN MAHAKAM ULU - Pamilia Pidang (ADMINISTRASI PUBLIK, 2018)
This research is based on how the implementation of electronic KTP making in subdistrict long bagun Mahakam ulu district based on presidential regulation no. 67 in 2011.The purpose of this study is to determine the mechanism of e-ID card implementation based on Presidential Regulation No. 67 of 2011 in Long Bagun District Mahakam Ulu Regency. Type of research or explanation used is descriptive qualitative used to analyze research variables. Types of data used are kusioner, observation, interview, and documentation.From the results showed that the ability of personnel resources that handle e-ID card is less optimal and less ready in serving the community, Lack of good service delivery by the operator operators to the society, Socialization conducted by the District Government of Long Bagun not well done, so the lack of information accepted by citizens of Long Bagun.The obstacles encountered in the implementation of making Electronic Identity Card that is in the procurement of equipment and the lack of provision given to the operator in charge of making the Cards of Elekronic Marking then less discipline civil state apparatus in charge and assist the community in making Electronic Identity Card.